EFFECTS OF SAWING PATTERN ON DRYING RATE AND RESIDUAL DRYING STRESSES OF PINUS RADIATA LUMBER - S Pang; A.N Haslett (Maderas: Ciencia y Tecnología, 2002)
Flatsawn and quartersawn Pinus radiata (radiata pine) sapwood boards were dried in a tunnel dryer in three runs using three drying schedules. These schedules represented low temperature (LT), accelerated conventional temperature (ACT) and high temperature (HT) drying. In each run, the boards were assembled in the dryer in two vertically matched layers with the flatsawn and the quartersawn boards being alternatively placed side by side. The samples were weighed at pre-set drying times. After drying, all of the samples were cut to two halves, one half for oven drying to determine the moisture content during drying and the remaining half for stress assessments. For LT and ACT drying, the quartersawn boards dried slower than the flatsawn boards, but for HT drying the difference between the quartersawn and the flatsawn boards was not statistically significant. The transverse residual drying stress in the quartersawn boards was, in general, lower than the flatsawn boards and the difference was most apparent for the LT drying